Healthcare Associated Infections and Antimicrobial Use in the Neonatal Unit at the Dalal Jamm National Hospital, Senegal - Fall, Awa; Diouf, Ndeye Marieme; Ndour, Daouda; Tine, Alioune; Ba, Abou; Ba, Awa; Fortes, Louise; Badiane, Aida Sadikh (British Journal of Healthcare and Medical Research, 2025)
Introduction: Healthcare-associated infections (HAIs) represent a significant public health concern, as they have been associated with prolonged hospital stays and deteriorated patient prognoses. The objective of this study was to ascertain the prevalence of HAIs at the neonatology clinic, the microorganisms implicated, and the antibiotics employed for their treatment. Method: This prospective study was conducted at the Dalal Jamm National Hospital of Guédiawaye (CHNDJ) in Dakar, Senegal. Microorganisms were identified by culture and the automated Vitek II system for bacterial and a filamentation test for yeast. Data on antimicrobial treatment were collected. Results: The prevalence of HAIs was 36.2% (17/47), and a mortality of 21.3% (10/47). The microorganisms responsible for HAIs were mainly Klebsiella pneumoniae (36.1%), Staphylococcus aureus (22.2%), Escherichia coli (11.1%), Enterococcus spp. (8.3%), Candida albicans (5.6%), Pseudomonas aeruginosa (5.6%) and Acinetobacter baumannii (2.8%). Four families were most used; Cephalosporins, Fluoroquinolones, Aminosides and Carbopenems. Conclusion: HAIs are a frequent occurrence in the neonatology clinic at CHNDJ, and are responsible for a significant mortality rate. Consequently, there is an imperative for the implementation of an active surveillance system to facilitate the development of effective control and preventive interventions.